A high voltage lithium cobalt oxide positive electrode material and its preparation method and use
By doping elements in the lithium cobalt oxide positive electrode material and covering electronic ferroelectrics, the problems of existing materials' structural deterioration and poor electrochemical performance at high temperatures are solved, and the demand for higher electrochemical performance and higher voltages is achieved.
Patent Information
- Application Number
- CN202110990716.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-26
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2041-08-26
AI Technical Summary
The existing high-voltage lithium cobalt oxide cathode materials are prone to agglomeration, compressed depolymerization of materials, compressed deformation and cracking of materials during synthesis and processing, resulting in poor electrochemical performance and difficult to meet the needs of higher voltages.
By doping elements of specific types and contents in the lithium cobalt oxide matrix and covering the surface with the electron ferroelectric RFe2O4, the predoping uniformity of the lithium cobalt oxide positive electrode material is improved, particle aggregation is reduced, compaction density and impedance of the electrode/electrolyte interface are improved.
It significantly improves the high-temperature cycle stability and rate performance of lithium cobalt oxide positive electrode material, meeting the demand for 4.55V high-voltage lithium cobalt oxide.
Smart Images

Figure CN115719810B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion battery positive electrode materials, and in particular to a high-voltage lithium cobalt oxide positive electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of electronic products, the market demand for renewable energy with small size, high energy and long cycle life is increasing. Lithium-ion batteries have been widely used in electronic devices due to their advantages such as high voltage, high energy and light weight. Lithium cobalt oxide is a commonly used positive electrode material for lithium-ion batteries. Its theoretical capacity is 274mAh / g, but in actual use, the charging cut-off voltage is lower than 4.2V, and only half of the lithium is extracted and embedded, so its actual capacity is only about 145mAh / g. At present, in order to improve the electrochemical properties of lithium cobalt oxide positive electrode materials, the research focus has gradually shifted to the preparation of high-voltage lithium cobalt oxide positive electrode materials.
[0003] CN103490063A discloses a method for preparing modified lithium cobalt oxide, which maintains the high-voltage stability of lithium cobalt oxide by doping manganese. However, a thicker inert oxide layer is used to coat the lithium cobalt oxide, which affects the transmission of lithium ions and reduces the conductivity and specific capacity.
[0004] CN105406036A discloses a high-voltage lithium cobalt oxide positive electrode material for lithium-ion batteries and a preparation method thereof. A lithium cobalt oxide matrix is doped with a rare earth halogen compound and the matrix is coated with a halogen-containing compound to obtain a compaction density of 4.5 g / m 3 4.55V high-voltage lithium cobalt oxide positive electrode material; however, the large-particle lithium cobalt oxide prepared by this method lacks a certain grading ratio of small-particle lithium cobalt oxide to ensure rate performance. A portion of the lithium cobalt oxide in the resulting product is agglomerated by a number of small particles with a particle size of 5-20μm, which is prone to depolymerization during the rolling process of the positive electrode sheet, exposing the fresh surface of the matrix and the internal grain boundaries, thereby generating a large number of material defects, weakening material performance, and making it difficult to adapt to the needs of the development of the high-voltage lithium cobalt oxide market.
[0005] CN103746114B discloses a method for preparing a lithium cobalt oxide positive electrode material, which prepares a cobalt oxide precursor with a reasonable combination of large, medium and small particles, and further synthesizes a lithium cobalt oxide positive electrode material with a reasonable combination of large, medium and small particles, so that the compaction density is significantly improved, and a 4.4V lithium cobalt oxide positive electrode material is obtained; however, the large, medium and small cobalt oxide particles are mixed and sintered with a lithium source, which will result in an excessively high lithium content of the cobalt oxide particles with medium and small particle sizes, and excessive lithium compounds will remain on the outer surfaces of the medium and small particles, which will promote interface fusion under excessively high temperature conditions and easily form abnormally large particles. At this time, in order to crush the large, medium and small lithium cobalt oxide particles with high bonding strength, the crushing strength must be increased, which is easy to cause excessive crushing. Therefore, the lithium cobalt oxide material synthesized using this production process is difficult to adapt to the development needs of higher voltage lithium cobalt oxide.
[0006] The lithium cobalt oxide positive electrode materials reported above are difficult to adapt to the development needs of higher voltage lithium cobalt oxide. At the same time, problems such as agglomeration, material depolymerization under pressure, material deformation and cracking under pressure may occur during the synthesis and processing process, as well as the problem of low material compaction due to poor particle size distribution and excessive porosity of particle accumulation, which affects the electrochemical properties of lithium cobalt oxide positive electrode materials.
[0007] Therefore, how to solve the above problems and prepare high-voltage lithium cobalt oxide positive electrode materials with better electrochemical performance has become an urgent problem to be solved. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-voltage lithium cobalt oxide positive electrode material and its preparation method and use. The present invention can improve the uniformity of lithium cobalt oxide pre-doping, reduce the agglomeration of lithium cobalt oxide particles, improve the consistency of large particle single crystal particle size, increase the compaction density, reduce overpressure deformation and improve the interface impedance of the electrode / electrolyte, and further improve the high-temperature cycle stability and rate performance of the lithium cobalt oxide positive electrode material.
[0009] The "high voltage lithium cobalt oxide positive electrode material" in the present invention means that the retention rate of the positive electrode material is above 90% after 80 cycles under the test conditions of 4.55V voltage and 45°C temperature.
[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a lithium cobalt oxide positive electrode material, in particular, a high voltage lithium cobalt oxide positive electrode material, the lithium cobalt oxide positive electrode material comprises a doped lithium cobalt oxide matrix and a coating body coated on the doped lithium cobalt oxide matrix, the general formula of the doped lithium cobalt oxide matrix is LiCo 1-x-y A x B yO2, wherein 0.015≤x≤0.045, 0.0001≤y≤0.002, A is Al, and B is any one or a combination of at least two of the elements La, Ce, Pr, Nd, Er, Zr, Nb, Sr, V, Ba, Ca, Na and K; and the coating is a ferroelectric.
[0012] The present invention uses specific types and contents of doping elements to perform bulk doping on a lithium cobalt oxide matrix and uses ferroelectrics for surface coating, which can solve the problem of structural deterioration at high temperatures, and at the same time can improve the interface impedance of the electrode / electrolyte, reduce voltage polarization, and improve rate performance, thus meeting the demand for 4.55V high-voltage lithium cobalt oxide.
[0013] The LiCo provided by the present invention 1-x-y A x B y In O2, 0.015≤x≤0.045, for example, it can be 0.015, 0.025, 0.035 or 0.045, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0014] The LiCo provided by the present invention 1-x-y A x B y In O2, 0.0001≤y≤0.002, for example, it can be 0.0001, 0.0005, 0.001, 0.0015 or 0.002, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0015] Preferably, the ferroelectric is an electronic ferroelectric. By coating the surface of the doped lithium cobalt oxide substrate with the electronic ferroelectric, the rate performance can be further improved to meet the requirements of 4.55V high-voltage lithium cobalt oxide.
[0016] Preferably, the general formula of the electronic ferroelectric is RFe2O4, wherein R is any one of Lu, Y, Yb or Er, or a combination of at least two of them, and RFe2O4 may be, for example, LuFe2O4, YFe2O4, YbFe2O4 or ErFe2O4, etc. In the present invention, when coating the doped lithium cobalt oxide substrate, the electronic ferroelectric may be used as a single type or as a mixture of different types, for example, the electronic ferroelectric may be a combination of LuFe2O4 and YFe2O4, a combination of YFe2O4 and YbFe2O4, a combination of YbFe2O4 and ErFe2O4, or a combination of LuFe2O4, YFe2O4 and YbFe2O4, etc.
[0017] In the present invention, the electronic ferroelectric can improve the interface characteristics of the lithium cobalt oxide positive electrode material, and improve the high voltage resistance and cycle stability of the lithium cobalt oxide positive electrode material. In the charging and discharging process of the lithium ion battery, the main lithium insertion and delithiation reactions occur in the positive electrode material. Due to the huge difference between the transmission rate of lithium ions in the lithium cobalt oxide positive electrode matrix and the migration rate in the electrolyte, an adsorption layer of lithium ions is formed at the electrode / electrolyte interface, thereby generating a strong electric field. The continuous action of this strong electric field on the surface of the lithium cobalt oxide positive electrode particles causes polarization damage inside the lithium cobalt oxide positive electrode particles, resulting in battery performance attenuation. The present invention embeds a high dielectric electronic ferroelectric RFe2O4 between the lithium cobalt oxide positive electrode material matrix and the electrolyte interface. It exhibits huge dielectric relaxation in a low-frequency alternating current electric field, and the dielectric constant is as high as 5000, which can significantly reduce the field strength of the original strong electric field, alleviate the damage inside the particles of the lithium cobalt oxide positive electrode material, and improve the high voltage resistance performance of the lithium cobalt oxide positive electrode material. On the other hand, the electronic ferroelectric RFe2O4 used in the present invention is different from traditional ferroelectrics (such as ABO3 type ferroelectrics). When polarization occurs in traditional ferroelectrics, the structural position of their own anions and cations is generally changed, which will cause phase changes and changes in the unit cell volume, thereby generating internal stress between polycrystalline materials. Repeated reversible phase changes will also cause ferroelectric fatigue, causing the polarization characteristics of the ferroelectric to gradually decrease and disappear. The polarization phenomenon of the electronic ferroelectric RFe2O4 crystal in the electric field is caused by the mutual regulation of the charge properties of electrons, orbital hybridization and the spin freedom of electrons, and the effect of weakening the electric field strength can be achieved without the displacement polarization of anions and cations. Therefore, the electronic ferroelectric RFe2O4 used in this application is conducive to improving the high voltage resistance and cycle stability of lithium cobalt oxide positive electrode materials.
[0018] In the present invention, the electronic ferroelectric can also improve the rate performance of the lithium cobalt oxide positive electrode material. The doped lithium cobalt oxide positive electrode material is a layered structure compound, and the electronic ferroelectric with the general formula RFe2O4 also has a layered structure. The combination of these two layered structure compounds is conducive to the construction of ion channels, the deintercalation of lithium ions and the conduction of electrons and ions at the interface, so that the prepared doped lithium cobalt oxide positive electrode material has good ion migration ability and conductivity, and improves the rate performance of the lithium cobalt oxide positive electrode material.
[0019] Preferably, the doped lithium cobalt oxide matrix in the lithium cobalt oxide positive electrode material is a single crystal.
[0020] Preferably, the doped lithium cobalt oxide matrix includes large-particle lithium cobalt oxide and small-particle lithium cobalt oxide.
[0021] Preferably, the particle size of the large-particle lithium cobalt oxide is 15-25 μm, for example, it can be 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 18-23 μm.
[0022] Preferably, the particle size of the small-particle lithium cobalt oxide is 1-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 3-5 μm.
[0023] Preferably, the lithium cobalt oxide positive electrode material, based on the mass of the doped lithium cobalt oxide matrix as 100%, the content of the ferroelectric is 0.05-0.5%, for example, it can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 0.2-0.5%.
[0024] Preferably, the mass mixing ratio of the large-particle lithium cobalt oxide and the small-particle lithium cobalt oxide is z:(1-z), wherein 0.6≤z≤0.9, for example, it can be 0.6, 0.65, 0.7, 0.75, 0.8, 0.85 or 0.9, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The mass mixing ratio of the large-particle lithium cobalt oxide and the small-particle lithium cobalt oxide can specifically be 0.6:0.4, 0.65:0.35, 0.7:0.3, 0.75:0.25, 0.8:0.2, 0.85:0.15 or 0.9:0.1.
[0025] By combining large-particle lithium cobalt oxide and small-particle lithium cobalt oxide, the compaction density of the material can be increased and the rate performance can be improved.
[0026] In a second aspect, the present invention provides a method for preparing the lithium cobalt oxide positive electrode material as described in the first aspect, the preparation method comprising the following steps:
[0027] (1) preparing a doped lithium cobalt oxide polycrystalline material, wherein the doping elements in the doped lithium cobalt oxide polycrystalline material are A and B;
[0028] (2) The doped lithium cobalt oxide polycrystalline material described in step (1) is mixed with a ferroelectric and then sintered to obtain the lithium cobalt oxide positive electrode material.
[0029] Preferably, the doped lithium cobalt oxide polycrystalline material in step (1) comprises polycrystalline large lithium cobalt oxide and polycrystalline small lithium cobalt oxide.
[0030] Preferably, the method for preparing polycrystalline lithium cobalt oxide comprises the following steps:
[0031] a) mixing a large-particle cobalt source, a soluble A salt, a soluble B salt and a lithium source to obtain a first mixture;
[0032] b) sintering the first mixture to obtain polycrystalline lithium cobalt oxide.
[0033] Preferably, the method for preparing polycrystalline lithium cobalt oxide comprises the following steps:
[0034] a') mixing a small particle size cobalt source, a soluble A salt, a soluble B salt and a lithium source to obtain a second mixture;
[0035] b') then sintering the second mixture to obtain polycrystalline lithium cobalt oxide.
[0036] The present invention has no requirement on the preparation order of polycrystalline large lithium cobalt oxide and polycrystalline small lithium cobalt oxide. Either the polycrystalline large lithium cobalt oxide or the polycrystalline small lithium cobalt oxide can be prepared first.
[0037] Preferably, the particle size of the large-particle cobalt source in step a) is 15-25 μm, for example, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the particle size of the small-particle cobalt source in step a') is 1-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] Preferably, the large-particle cobalt source in step a) and the small-particle cobalt source in step a') are both cobalt tetraoxide.
[0040] Preferably, the cobalt oxide is spherical in shape and has pores inside. The cobalt oxide is spherical in shape, which can ensure that the lithium cobalt oxide synthesized therefrom has a large packing density, and has pores inside, which is conducive to the infiltration and absorption of the salt solution containing the doping element.
[0041] Preferably, the soluble A salts described in step a) and step a') are independently aluminum acetate and / or aluminum nitrate, and the soluble B salts are independently any one or a combination of at least two of acetates or nitrates of La, Ce, Pr, Nd, Er, Zr, Nb, Sr, V, Ba, Ca, Na, and K. For example, it can be a combination of lanthanum acetate, vanadium acetate, strontium acetate, strontium nitrate, barium nitrate, vanadium nitrate, a combination of vanadium acetate and sodium acetate, a combination of vanadium nitrate and sodium nitrate, a combination of neodymium nitrate and erbium nitrate, a combination of aluminum acetate and niobium nitrate, a combination of aluminum nitrate and niobium acetate, a combination of zirconium acetate and barium nitrate, or a combination of praseodymium acetate, niobium nitrate, and calcium nitrate, etc.
[0042] In the present invention, the term "independently" means that the two selections do not interfere with each other. For example, the soluble A salts described in step a) and step a') are independently aluminum acetate and / or aluminum nitrate, which means that when the soluble A salt described in step a) is aluminum acetate, the soluble A salt described in step a') can be aluminum acetate or aluminum nitrate, and the selection of the soluble A salt in step a) does not interfere with the selection of the soluble A salt in step a').
[0043] Preferably, the lithium sources described in step a) and step a') are independently any one or a combination of at least two of lithium carbonate, lithium hydroxide, lithium oxide, lithium oxalate, or lithium peroxide. For example, it can be a combination of lithium carbonate, lithium hydroxide, lithium oxide, lithium oxalate, lithium peroxide, a combination of lithium carbonate and lithium hydroxide, a combination of lithium oxalate and lithium peroxide, a combination of lithium oxide and lithium oxalate, or a combination of lithium carbonate, lithium hydroxide, lithium oxide, and lithium oxalate.
[0044] Preferably, the lithium source is preferably a combination of two of lithium carbonate, lithium hydroxide, and lithium oxide, and the mass ratio of the two substances is σ:(1 - σ), where 0.5 ≤ σ < 1. For example, it can be a combination of lithium carbonate and lithium hydroxide in a mass ratio of 0.9:0.1, 0.8:0.2, 0.7:0.3, 0.6:0.4, or 0.5:0.5.
[0045] Preferably, the lithium source is a combination of three of lithium carbonate, lithium hydroxide, and lithium peroxide, and the mass ratio of the three substances is m:n:(1 - m - n), where 0.5 ≤ m < 1 and 0 < n < 0.5. For example, it can be a combination of lithium carbonate, lithium hydroxide, and lithium peroxide in a mass ratio of 0.9:0.08:0.02, 0.8:0.15:0.05, 0.7:0.2:0.1, 0.6:0.28:0.12, or 0.5:0.35:0.15.
[0046] Preferably, the mixing in step a) is carried out in the following manner: the raw materials other than the lithium source are mixed in the liquid phase, and after flash evaporation, they are mixed with the lithium source.
[0047] In an optional embodiment, the mixing in step a) is performed in the following manner: the large particle size cobalt source, the soluble A salt and the soluble B salt are mixed in liquid phase, and then mixed with the lithium source after flash evaporation.
[0048] Preferably, the mixing in step a') is performed in the following manner: the raw materials other than the lithium source are mixed in liquid phase, and then mixed with the lithium source after flash evaporation.
[0049] In an optional embodiment, the mixing in step a') is performed in the following manner: a small particle size cobalt source, a soluble A salt and a soluble B salt are mixed in liquid phase, and then mixed with a lithium source after flash evaporation.
[0050] Preferably, the solid content of the slurry in the liquid phase mixing step in step a) and step a') is independently 60-90%, for example, it can be 60%, 65%, 70%, 75%, 80%, 85% or 90%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] The present invention uses a liquid phase mixing method to perform bulk phase doping on the cobalt source, and adopts a flash drying method at the same time, using a universal flash dryer to achieve rapid drying, dehydration and mixed dispersion, which can make the doping elements and the cobalt source dispersed more evenly and have high sphericity. After mixing, the pores in the material can be effectively reduced, and the structural stability and compaction density of the material can be improved at the same time.
[0052] Preferably, the sintering in step b) and step b') is carried out in an air atmosphere, and the air flow rate of the sintering is independently 0.8-2.0 L / (min·m 3 ), for example, it can be 0.8L / (min·m 3 )、1.0L / (min·m 3 )、1.2L / (min·m 3 )、1.4L / (min·m 3 )、1.6L / (min·m 3 )、1.8L / (min·m 3 ) or 2.0L / (min·m 3 ), but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] Preferably, the heating rates of the sintering in step b) and step b') are independently 5-10°C / min, for example, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, the sintering temperature in step b) and step b') is independently 400-800°C, for example, 400°C, 500°C, 600°C, 700°C or 800°C, but is not limited to the listed values, and other values not listed in the numerical range are also applicable; the sintering time is independently 1-5h, for example, 1h, 2h, 3h, 4h or 5h, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0055] Preferably, the sintering in step (2) is carried out in an air atmosphere.
[0056] Preferably, the air flow rate of the sintering in step (2) is 0.2-1.0 L / (min·m 3 ), for example, it can be 0.2L / (min·m 3 )、0.4L / (min·m 3 )、0.6L / (min·m 3 )、0.8L / (min·m 3 ) or 1.0L / (min·m 3 ), but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] Preferably, the heating rate of the sintering in step (2) is 1-6°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or 6°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] Preferably, the sintering temperature in step (2) is 800-1100°C, for example, it can be 800°C, 900°C, 1000°C or 1100°C, but is not limited to the listed values, and other values not listed in the numerical range are also applicable, preferably 950-1100°C; the sintering time is 5-20h, for example, it can be 5h, 8h, 10h, 15h or 20h, but is not limited to the listed values, and other values not listed in the numerical range are also applicable, preferably 12-16h.
[0059] In the present invention, the sintering described in step (2) controls the sintering temperature and time and other factors to recrystallize the polycrystalline large lithium cobalt oxide and the polycrystalline small lithium cobalt oxide at high temperature, eliminate the grain boundaries, and prepare single-crystal lithium cobalt oxide particles with better particle size distribution consistency, which can effectively reduce the generation of material defects such as abnormally large single crystals and agglomerate polycrystalline particles, while reducing the problem of abnormally large single crystal overpressure deformation and agglomerate depolymerization. Moreover, during the sintering process, the bonding between the ferroelectric and the lithium cobalt oxide matrix can be improved. The combined effect of the above factors can significantly improve the specific capacity, cycle stability and rate performance.
[0060] As a further preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0061] (1) A cobalt source with a particle size of 15-25 μm, a soluble A salt and a soluble B salt are mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 60-90%, the slurry is flash-dried and then mixed with a lithium source, and then the mixture is sintered in an air atmosphere at 400-800° C. for 1-5 h, the sintering heating rate is 5-10° C. / min, and the air flow rate is 0.8-2.0 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 25-100°C to obtain polycrystalline lithium cobalt oxide;
[0062] A cobalt source with a particle size of 1-5 μm, a soluble A salt and a soluble B salt are mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 60-90%, the slurry is flash-dried and then mixed with a lithium source, and then the mixture is sintered in an air atmosphere at 400-800° C. for 1-5 hours, the sintering heating rate is 5-10° C. / min, and the air flow rate is 0.8-2.0 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 25-100°C to obtain polycrystalline lithium cobalt oxide;
[0063] Polycrystalline large cobalt oxide and polycrystalline small cobalt oxide have the same composition, and both have the general formula LiCo 1-x-y A x B y O2, wherein 0.015≤x≤045, for example, it can be 0.015, 0.025, 0.035 or 0.045, 0.0005≤y≤0.002, for example, it can be 0.0005, 0.001, 0.0015 or 0.002, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, A is Al, B is any one of La, Ce, Pr, Nd, Er, Zr, Nb, Sr, V, Ba, Ca, Na and K elements, or a combination of at least two of them.
[0064] Wherein, the soluble A salt is aluminum acetate and / or aluminum nitrate, and the soluble B salt is any one or a combination of at least two of the acetates or nitrates of La, Ce, Pr, Nd, Er, Zr, Nb, Sr, V, Ba, Ca, Na and K;
[0065] (2) The polycrystalline large cobalt oxide and the polycrystalline small cobalt oxide described in step (1) are graded, and then added to the coating body for mixing, and the mixture is sintered in an air atmosphere at 800-1100° C. for 5-20 h, with a sintering heating rate of 1-6° C. / min and an air flow rate of 0.2-1.0 L / (min·m3 ), and naturally cool to room temperature after sintering to obtain the lithium cobalt oxide positive electrode material.
[0066] The present invention separately prepares doping-optimized polycrystalline small lithium cobalt oxide and polycrystalline large lithium cobalt oxide in step (1), mixes the two in a certain proportion, and mixes the coating at the same time. The lithium cobalt oxide semi-finished product prepared by this method has high sphericity, can effectively reduce the pores in the material after mixing, can adjust the gradation ratio of large and small particles in a wide range, and obtain materials with different rates and compaction properties; at the same time, coating the electronic ferroelectric can further improve the rate performance and meet the needs of 4.55V high-voltage lithium cobalt oxide. While continuously improving the bulk phase doping and surface coating, this method also reduces the material defects in the synthesis process and subsequent processing process as much as possible, and can simultaneously improve the compaction density, cycle stability and improve the rate performance.
[0067] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises the lithium cobalt oxide positive electrode material as described in the first aspect.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] (1) The present invention uses a specific type and content of doping elements to perform bulk doping on the lithium cobalt oxide matrix and uses ferroelectrics for surface coating, which can solve the problem of structural deterioration under high temperature, and at the same time can improve the interface impedance of the electrode / electrolyte, reduce voltage polarization, and improve the rate performance, meeting the demand for 4.55V high-voltage lithium cobalt oxide.
[0070] (2) In the process of bulk doping of the matrix, the present invention preferably uses liquid phase mixing and flash drying to mix the materials, which improves the uniformity and sphericity of bulk element doping and further improves the structural stability of the material.
[0071] (3) The present invention preferably prepares large polycrystalline lithium cobalt oxide and small polycrystalline lithium cobalt oxide separately, and mixes the electronic ferroelectric in a certain proportion. Since the semi-finished lithium cobalt oxide has a high sphericity, the pores in the material can be effectively reduced after mixing. After high-temperature recrystallization, single-crystalline lithium cobalt oxide particles with better consistency in particle size distribution can be prepared, which effectively reduces the generation of material defects such as abnormally large single crystals and agglomerated polycrystalline particles, and further improves the compaction density, cycle stability and rate performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 and Figure 2 This is a SEM image of cobalt tetroxide in Example 1 of the present invention.
[0073] Figure 3 This is a SEM image of the polycrystalline lithium cobalt oxide of Example 1 of the present invention.
[0074] Figure 4 This is a SEM image of the polycrystalline lithium cobalt oxide according to Example 1 of the present invention. DETAILED DESCRIPTION
[0075] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0076] Example 1
[0077] The present embodiment provides a lithium cobalt oxide positive electrode material, which includes a doped lithium cobalt oxide matrix and a coating coated on the doped lithium cobalt oxide matrix, wherein the doped lithium cobalt oxide matrix is LiCo 0.9744 Al 0.025 Nb 0.0006 O2, the doped lithium cobalt oxide matrix is a single crystal, the coating is LuFe2O4, and the content of ferroelectric is 0.3% based on the mass of the doped lithium cobalt oxide matrix being 100%; the doped lithium cobalt oxide matrix includes large-particle lithium cobalt oxide and small-particle lithium cobalt oxide, wherein the particle size of the large-particle lithium cobalt oxide is 20μm, and the particle size of the small-particle lithium cobalt oxide is 4.5μm; the mass mixing ratio of large-particle lithium cobalt oxide and small-particle lithium cobalt oxide is 0.75:0.25.
[0078] The preparation method of the lithium cobalt oxide positive electrode material of this embodiment comprises the following steps:
[0079] (1) Cobalt oxide with a particle size of 20 μm (purchased from Gemstar Technology China Co Ltd, battery-grade spherical cobalt oxide), aluminum acetate and niobium nitrate were mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 75%. The slurry was flash-dried and then mixed with lithium carbonate. The mixture was then sintered in an air atmosphere at 600° C. for 3 h. The sintering heating rate was 8° C. / min. The air flow rate was 1.5 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 50° C. to obtain polycrystalline lithium cobalt oxide; wherein the SEM image of the cobalt oxide used is shown in Figure 1 and Figure 2 The cobalt source is spherical cobalt oxide, which contains pores. Its spherical shape ensures that the lithium cobalt oxide synthesized subsequently has a large packing density, and its pore structure is conducive to the infiltration and absorption of the salt solution of the doping element; the SEM image of polycrystalline lithium cobalt oxide is shown in Figure 3 ,It can be seen from the figure that the polycrystalline large lithium cobalt oxide particles and the interfaces between particles are separated from each other and have not grown and fused into abnormally large particles;
[0080] Cobaltous oxide with a particle size of 4.5 μm, aluminum nitrate and niobium acetate were mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 75%. The slurry was flash dried and then mixed with lithium hydroxide. The mixture was then sintered in an air atmosphere at 600° C. for 3 h. The sintering heating rate was 8° C. / min. The air flow rate was 1.5 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 50°C to obtain polycrystalline lithium cobalt oxide, the SEM image of which is shown in Figure 4 ,It can be seen from the figure that the polycrystalline small lithium cobalt oxide particles and ,the interfaces between the particles are separated from each other and have not ,grown and fused into abnormally large particles.
[0081] The composition of polycrystalline large lithium cobalt oxide and polycrystalline small lithium cobalt oxide is the same;
[0082] (2) The polycrystalline large cobalt oxide and the polycrystalline small cobalt oxide described in step (1) are graded, and then LuFe2O4 is added and mixed, and the mixture is sintered in an air atmosphere at 950° C. for 15 h, with a sintering heating rate of 4° C. / min and an air flow rate of 0.6 L / (min·m 3 ), and naturally cool to room temperature after sintering to obtain the lithium cobalt oxide positive electrode material.
[0083] Example 2
[0084] The present embodiment provides a lithium cobalt oxide positive electrode material, which includes a doped lithium cobalt oxide matrix and a coating coated on the doped lithium cobalt oxide matrix, wherein the doped lithium cobalt oxide matrix is LiCo 0.978 Al 0.018 V 0.0003 Na 0.001 O2, the coating is LuFe2O4, YFe2O4 and YbFe2O4, the mass ratio of these three coatings is LuFe2O4:YFe2O4:YbFe2O4=1:1:1, the mass of the doped lithium cobalt oxide matrix is 100%, and the content of ferroelectric is 0.05%; the doped lithium cobalt oxide matrix includes large-particle lithium cobalt oxide and small-particle lithium cobalt oxide, wherein the particle size of the large-particle lithium cobalt oxide is 18μm, and the particle size of the small-particle lithium cobalt oxide is 3μm; the mass mixing ratio of large-particle lithium cobalt oxide and small-particle lithium cobalt oxide is 0.6:0.4.
[0085] The preparation method of the lithium cobalt oxide positive electrode material of this embodiment comprises the following steps:
[0086] (1) Cobaltous oxide with a particle size of 18 μm, aluminum nitrate, vanadium acetate and sodium acetate are mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 60%, the slurry is flash-dried and then mixed with lithium carbonate, lithium hydroxide, lithium oxide and lithium oxalate, and then the mixture is sintered in an air atmosphere at 400° C. for 5 h, the sintering heating rate is 5° C. / min, and the air flow rate is 0.8 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 25°C to obtain polycrystalline lithium cobalt oxide;
[0087] Cobaltous oxide with a particle size of 3 μm, aluminum acetate, vanadium nitrate and sodium nitrate were mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 90%. The slurry was flash dried and then mixed with lithium hydroxide. The mixture was then sintered in an air atmosphere at 800°C for 1 hour. The sintering heating rate was 10°C / min and the air flow rate was 2.0 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 100°C to obtain polycrystalline lithium cobalt oxide;
[0088] The composition of polycrystalline large lithium cobalt oxide and polycrystalline small lithium cobalt oxide is the same;
[0089] (2) The polycrystalline large cobalt oxide and the polycrystalline small cobalt oxide described in step (1) are graded, and then LuFe2O4, YFe2O4 and YbFe2O4 are added and mixed, and the mixture is sintered in an air atmosphere at 800° C. for 20 h, with a sintering heating rate of 1° C. / min and an air flow rate of 1.0 L / (min·m 3 ), and naturally cool to room temperature after sintering to obtain the lithium cobalt oxide positive electrode material.
[0090] Example 3
[0091] This embodiment provides a lithium cobalt oxide positive electrode material, which includes a doped lithium cobalt oxide matrix and a coating coated on the doped lithium cobalt oxide matrix. The general formula of the doped lithium cobalt oxide matrix is LiCo 0.9634 Al 0.035 Pr 0.0002 Ca 0.001 Nb 0.0004 O2, the coating is LuFe2O4 and YFe2O4, the mass ratio of these two coatings is LuFe2O4:YFe2O4=1:1, the mass of the doped lithium cobalt oxide matrix is 100%, and the content of ferroelectric is 0.07%; the doped lithium cobalt oxide matrix includes large-particle lithium cobalt oxide and small-particle lithium cobalt oxide, wherein the particle size of the large-particle lithium cobalt oxide is 25μm, and the particle size of the small-particle lithium cobalt oxide is 5μm; the mass mixing ratio of large-particle lithium cobalt oxide and small-particle lithium cobalt oxide is 0.8:0.2.
[0092] The preparation method of the lithium cobalt oxide positive electrode material of this embodiment comprises the following steps:
[0093] (1) Cobaltous oxide with a particle size of 25 μm, aluminum acetate, praseodymium acetate, niobium nitrate and calcium nitrate are mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 90%, the slurry is flash-dried and then mixed with lithium carbonate, and then the mixture is sintered in an air atmosphere at 800° C. for 1 h, the sintering heating rate is 10° C. / min, and the air flow rate is 2.0 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 100°C to obtain polycrystalline lithium cobalt oxide;
[0094] Cobaltous oxide with a particle size of 5 μm, aluminum nitrate, praseodymium acetate, niobium nitrate and calcium nitrate are mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 60%. The slurry is flash-dried and then mixed with lithium carbonate and lithium hydroxide. The mixture is then sintered in an air atmosphere at 400° C. for 5 h. The sintering heating rate is 5° C. / min and the air flow rate is 0.8 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 25°C to obtain polycrystalline lithium cobalt oxide;
[0095] The composition of polycrystalline large lithium cobalt oxide and polycrystalline small lithium cobalt oxide is the same;
[0096] (2) The polycrystalline large cobalt oxide and the polycrystalline small cobalt oxide described in step (1) are graded, and then LuFe2O4 and YFe2O4 are added and mixed, and the mixture is sintered in an air atmosphere at 1100° C. for 5 h, with a sintering heating rate of 6° C. / min and an air flow rate of 0.2 L / (min·m 3 ), and naturally cool to room temperature after sintering to obtain the lithium cobalt oxide positive electrode material.
[0097] Example 4
[0098] The present embodiment provides a lithium cobalt oxide positive electrode material, which includes a doped lithium cobalt oxide matrix and a coating coated on the doped lithium cobalt oxide matrix, wherein the doped lithium cobalt oxide matrix is LiCo 0.965 Al 0.033 V 0.002 O2, the coating is YbFe2O4, and the content of ferroelectric is 0.2% based on the mass of the doped lithium cobalt oxide matrix being 100%; the doped lithium cobalt oxide matrix includes large-particle lithium cobalt oxide and small-particle lithium cobalt oxide, wherein the particle size of the large-particle lithium cobalt oxide is 13μm, and the particle size of the small-particle lithium cobalt oxide is 0.5μm; the mass mixing ratio of large-particle lithium cobalt oxide and small-particle lithium cobalt oxide is 0.65:0.35.
[0099] The preparation method of the lithium cobalt oxide positive electrode material of this embodiment comprises the following steps:
[0100] (1) Cobaltous oxide with a particle size of 13 μm, aluminum acetate and vanadium nitrate are mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 80%, the slurry is flash-dried and then mixed with lithium carbonate, and the mixture is sintered in an air atmosphere at 450° C. for 4 h, the sintering heating rate is 6° C. / min, and the air flow rate is 1.0 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 50°C to obtain polycrystalline lithium cobalt oxide;
[0101] Cobaltous oxide with a particle size of 0.5 μm, aluminum nitrate and vanadium acetate are mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 65%. The slurry is flash-dried and then mixed with lithium hydroxide. The mixture is then sintered in an air atmosphere at 650° C. for 2 h. The sintering heating rate is 7° C. / min and the air flow rate is 1.8 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 70°C to obtain polycrystalline lithium cobalt oxide;
[0102] The composition of polycrystalline large lithium cobalt oxide and polycrystalline small lithium cobalt oxide is the same;
[0103] (2) The polycrystalline large cobalt oxide and the polycrystalline small cobalt oxide described in step (1) are graded, and then YbFe2O4 is added and mixed. The mixture is sintered in an air atmosphere at 850° C. for 12 h, with a sintering heating rate of 6° C. / min and an air flow rate of 0.7 L / (min·m 3 ), and naturally cool to room temperature after sintering to obtain the lithium cobalt oxide positive electrode material.
[0104] Example 5
[0105] This embodiment provides a lithium cobalt oxide positive electrode material, which includes a doped lithium cobalt oxide matrix and a coating coated on the doped lithium cobalt oxide matrix. The general formula of the doped lithium cobalt oxide matrix is LiCo 0.976 Al 0.022 Zr 0.0011 Ba 0.0009 O2, the coating is YFe2O4 and YbFe2O4, the mass ratio of these two coatings is YFe2O4:YbFe2O4=1:1, the mass of the doped lithium cobalt oxide matrix is 100%, and the content of ferroelectric is 0.4%; the doped lithium cobalt oxide matrix includes large-particle lithium cobalt oxide and small-particle lithium cobalt oxide, wherein the particle size of the large-particle lithium cobalt oxide is 27μm, and the particle size of the small-particle lithium cobalt oxide is 7μm; the mass mixing ratio of large-particle lithium cobalt oxide and small-particle lithium cobalt oxide is 0.82:0.18.
[0106] The preparation method of the lithium cobalt oxide positive electrode material of this embodiment comprises the following steps:
[0107] (1) Cobaltous oxide with a particle size of 27 μm, aluminum nitrate, zirconium acetate and barium nitrate were mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 75%, the slurry was flash dried and then mixed with lithium carbonate, and the mixture was sintered in an air atmosphere at 750° C. for 3 h, the sintering heating rate was 5° C. / min, and the air flow rate was 1.7 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 65°C to obtain polycrystalline lithium cobalt oxide;
[0108] Cobaltous oxide with a particle size of 7 μm, aluminum nitrate, zirconium acetate and barium nitrate were mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 85%. The slurry was flash dried and then mixed with lithium hydroxide. The mixture was then sintered in an air atmosphere at 750° C. for 3 h. The sintering heating rate was 10° C. / min and the air flow rate was 1.8 L / (min·m 3 ), after sintering, the temperature is naturally lowered to 100°C to obtain polycrystalline lithium cobalt oxide;
[0109] The composition of polycrystalline large lithium cobalt oxide and polycrystalline small lithium cobalt oxide is the same;
[0110] (2) The polycrystalline large cobalt oxide and the polycrystalline small cobalt oxide described in step (1) are graded, and then YFe2O4 and YbFe2O4 are added and mixed, and the mixture is sintered in an air atmosphere at 1000° C. for 2 h, with a sintering heating rate of 6° C. / min and an air flow rate of 0.2 L / (min·m 3 ), and naturally cool to room temperature after sintering to obtain the lithium cobalt oxide positive electrode material.
[0111] Example 6
[0112] This embodiment provides a lithium cobalt oxide positive electrode material and a preparation method thereof, which is the same as that of Embodiment 1 except that the coating body is BaTiO3.
[0113] Example 7
[0114] This embodiment provides a lithium cobalt oxide positive electrode material and a preparation method thereof, which is the same as that of Embodiment 1 except that the content of the ferroelectric is 0.045%.
[0115] Example 8
[0116] This embodiment provides a lithium cobalt oxide positive electrode material and a preparation method thereof, which is the same as that of Embodiment 1 except that the content of the ferroelectric is 0.7%.
[0117] Example 9
[0118] This embodiment provides a lithium cobalt oxide positive electrode material and a preparation method thereof, which is the same as that of Embodiment 1 except that the cobalt source, aluminum acetate, lanthanum nitrate and lithium carbonate are mixed in the following manner:
[0119] Cobaltous oxide, aluminum acetate, strontium nitrate and lithium carbonate with a particle size of 20 μm are dry-mixed by ball milling to obtain a mixture.
[0120] Example 10
[0121] This embodiment provides a lithium cobalt oxide positive electrode material and a preparation method thereof, which is the same as that of Embodiment 1 except that the sintering temperature in step (2) is 780° C.
[0122] Embodiment 11
[0123] This embodiment provides a lithium cobalt oxide positive electrode material and a preparation method thereof, which is the same as that of Embodiment 1 except that the sintering temperature in step (2) is 1150°C.
[0124] Example 12
[0125] This embodiment provides a lithium cobalt oxide positive electrode material and a preparation method thereof, which is the same as that of Embodiment 1 except that the sintering time in step (2) is 4.5 h.
[0126] Embodiment 13
[0127] This embodiment provides a lithium cobalt oxide positive electrode material and a preparation method thereof, which is the same as that of Embodiment 1 except that the sintering temperature in step (2) is 23h.
[0128] Embodiment 14
[0129] This embodiment provides a lithium cobalt oxide positive electrode material and a preparation method thereof, which is the same as that of Embodiment 1 except that the cobalt oxide with a particle size of 4.5 μm in step (1) is replaced by cobalt oxide with a particle size of 20 μm.
[0130] Comparative Example 1
[0131] This comparative example provides a lithium cobalt oxide positive electrode material, which is the same as Example 1 except that y is 0.005.
[0132] Comparative Example 2
[0133] This comparative example provides a lithium cobalt oxide positive electrode material, which is the same as Example 1 except that the coating body is Co(OH)2.
[0134] The lithium cobalt oxide positive electrode materials prepared in Examples 1-14 of the present invention and Comparative Examples 1-3 were assembled into batteries and subjected to electrochemical performance tests. The results of the electrode compaction density, rate performance, high temperature cycle performance, and room temperature accelerated test are shown in Table 1.
[0135] Preparation method of positive electrode sheet: Mix the prepared lithium cobalt oxide positive electrode material according to the mass ratio of lithium cobalt oxide positive electrode material: conductive carbon black Super-P: graphene: binder PVDF = 97.3:1:0.7:1, add N-methyl-2-pyrrolidone NMP solvent, stir evenly to obtain slurry. The slurry is evenly coated on both sides of the aluminum foil current collector, with a surface density of 44mg / cm 2 After vacuum drying, hot pressing and cutting, the positive electrode sheet is obtained for the test of the ultimate compaction density of the electrode sheet; the slurry is evenly coated on the single side of the aluminum foil current collector with a surface density of 22 mg / cm 2 After vacuum drying, hot pressing and cutting, the positive electrode sheet is obtained for assembling CR2032 button batteries.
[0136] Assembly method of CR2032 button battery: In an argon atmosphere glove box, assemble the positive electrode shell, gasket, positive electrode sheet, diaphragm, high voltage electrolyte, metal lithium sheet, gasket, spring, and negative electrode shell into a finished CR2032 button battery in sequence at an ambient temperature of 20°C and a dew point below -40°C. After assembly, let it stand for 2 hours at 50°C, then form it at an ambient temperature of 25°C and a dew point below -40°C, and then test the room temperature specific capacity, rate performance, and high temperature cycle.
[0137] Pole piece ultimate compaction density test method: The pole piece ultimate compaction density test is performed according to the method described in Chinese patent CN102564894A.
[0138] Normal temperature specific capacity and rate performance test conditions: stand at 25℃ ambient temperature for 2h, then charge to 4.55V at 0.1C rate, then charge at 4.55V constant voltage to current ≤0.015C or constant voltage time ≥40min. After standing for 10min, discharge at 0.1C rate to voltage ≤3.0V, thus obtaining 0.1C normal temperature specific capacity. After standing for 10min, charge to 4.55V at 0.1C rate, then charge to 4.55V at 4.55V constant voltage to current ≤0.015C or constant voltage time ≥40min, after standing for 10min, discharge at 2C rate to voltage ≤3.0V, thus obtaining 2C / 0.1C rate performance.
[0139] High temperature cycle performance test conditions: stand at 45°C ambient temperature for 30 minutes, then charge at 0.5C constant current to 4.55V, then charge at 4.55V constant voltage to current ≤0.025C or constant voltage time ≥40min. After standing for 10 minutes, discharge at 1C constant current to voltage ≤3.0V, which is recorded as one charge and discharge cycle. Stop the test when the cumulative number of cycles reaches 80, so as to obtain the retention rate of 80 cycles of high temperature cycles.
[0140] Table 1
[0141]
[0142]
[0143] analyze:
[0144] It can be seen from Examples 1-14 of the present invention that by using specific types and contents of doping elements to bulk-dope the lithium cobalt oxide matrix and using ferroelectrics for surface coating, the problem of structural deterioration at high temperatures can be solved. At the same time, the interface impedance of the electrode / electrolyte can be improved, the voltage polarization can be reduced, the rate performance and high-temperature cycle performance can be improved, and the demand for 4.55V high-voltage lithium cobalt oxide can be met.
[0145] By comparing Example 1 with Example 6, it can be seen that the different coatings in the lithium cobalt oxide positive electrode material will affect the electrochemical properties of the positive electrode material. Example 1 and Example 6 are coated with electronic ferroelectric LuFe2O4 and traditional ferroelectric BaTiO3 respectively. The ultimate compaction density, specific capacity and rate performance of the two are basically the same, but the high-temperature cycle performance is the most outstanding in the former. This is because the traditional ferroelectric BaTiO3 is mainly polarized by ion displacement, and is easy to polarize in the electric field generated by the charge and discharge cycle. At the same time, accompanied by the phase change of the grains, internal stress is generated in the lithium cobalt oxide particle coating layer. After multiple cycles, its polarization characteristics will weaken, and it will also cause the material volume to expand or shrink, destroying the stability of the coating layer, thereby causing the performance of the lithium cobalt oxide positive electrode material coated therewith to decline.
[0146] By comparing Example 1 with Examples 7-8, it can be seen that there is an optimal range for the coating content of the electronic ferroelectric LuFe2O4. As the coating amount gradually increases, the ultimate compaction density of the material remains basically unchanged, but the specific capacity of the positive electrode material gradually decreases, and the rate performance first increases and then tends to stabilize. Therefore, by adding an appropriate amount of coating, a lithium cobalt oxide positive electrode material with the best comprehensive capacity, rate and cycle performance can be obtained.
[0147] By comparing Example 1 with Example 9, it can be seen that dry mixing affects the uniformity of bulk doping, further resulting in a slight decrease in the ultimate compaction density of the lithium cobalt oxide positive electrode material, and a decrease in the specific capacity, rate and high-temperature cycle performance.
[0148] By comparing Example 1 with Examples 10-11, it can be seen that too low or too high secondary sintering temperature will lead to poor performance of lithium cobalt oxide positive electrode materials; when the secondary sintering temperature is too low, the lithium cobalt oxide positive electrode material particles are difficult to crystallize to form single-crystal lithium cobalt oxide particles, and are prone to form agglomerate particles. This type of positive electrode material is susceptible to roller depolymerization in subsequent processing steps, resulting in pole piece processing defects. Similarly, when the secondary sintering temperature is too high, the lithium cobalt oxide positive electrode material particles are prone to crystallization to form abnormally large lithium cobalt oxide particles. This type of pole material is susceptible to roller deformation in subsequent processing steps, and also produces pole piece processing defects.
[0149] By comparing Example 1 with Examples 12-13, it can be seen that too short or too long secondary sintering time will lead to poor performance of lithium cobalt oxide positive electrode materials; when the secondary sintering time is too short, the lithium cobalt oxide positive electrode material particles are difficult to crystallize into single-crystal lithium cobalt oxide particles, and are prone to form agglomerate particles. This type of positive electrode material is susceptible to roller depolymerization in subsequent processing steps, resulting in pole piece processing defects. Similarly, when the secondary sintering time is too long, the lithium cobalt oxide positive electrode material particles are prone to crystallization to form abnormally large lithium cobalt oxide particles. This type of pole material is susceptible to roller deformation in subsequent processing steps, and also produces pole piece processing defects.
[0150] By comparing Example 1 with Example 14, it can be seen that the ultimate compaction density and rate performance of the large single crystal lithium cobalt oxide positive electrode material alone are lower than those of Example 1, while the capacity and cycle performance are comparable to those of Example 1. This is because the large single crystal lithium cobalt oxide positive electrode material alone has more pores, and performs poorly in compaction density compared to the lithium cobalt oxide positive electrode material filled with small single crystals, which further leads to a significant reduction in its rate performance.
[0151] By comparing Example 1 with Comparative Example 1, it can be seen that the content of doping elements in the lithium cobalt oxide positive electrode material will affect the electrochemical properties of the lithium cobalt oxide positive electrode material. When the content of doping elements is too much, the overall performance of the lithium cobalt oxide positive electrode material is reduced. This is because excessive element doping can easily cause cation mixing, forming more lattice distortions in the lithium cobalt oxide crystals, affecting the normal embedding and extraction of lithium ions. At the same time, in the subsequent charge and discharge cycle process, internal stress is generated as the unit cell volume expands and contracts, which can easily cause grain pulverization, thereby reducing the performance of the lithium cobalt oxide positive electrode material.
[0152] By comparing Example 1 with Comparative Example 2, it can be seen that the type of coating in the lithium cobalt oxide positive electrode material will affect the electrochemical properties of the lithium cobalt oxide positive electrode material. When the coating is Co(OH)2, it is impossible to reduce the electric field generated at the electrode / electrolyte interface, alleviate the damage inside the particles of the lithium cobalt oxide positive electrode material, and construct ion channels, which is not conducive to the conduction of lithium ions between interfaces. Therefore, the electrochemical performance of the lithium cobalt oxide positive electrode material using the Co(OH)2 coating is reduced.
[0153] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A lithium cobalt oxide positive electrode material, characterized in that: The lithium cobaltate cathode material includes a doped lithium cobaltate matrix and a coating layer coated on the doped lithium cobaltate matrix. The general formula of the doped lithium cobaltate matrix is LiCo 1-x- y A x B y O2, where 0.015 ≤ x ≤ 0.045, 0 < y ≤ 0.002, A is Al, and B is any one or a combination of at least two of the elements La, Ce, Pr, Nd, Er, Zr, Nb, Sr, V, Ba, Ca, Na, and K; the coating layer is a ferroelectric body; The ferroelectric is an electronic ferroelectric; The general formula of the electronic ferroelectric is RFe2O4, wherein R is any one of Lu, Y, Yb or Er or a combination of at least two thereof.
2. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The doped lithium cobalt oxide matrix is a single crystal.
3. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The doped lithium cobalt oxide matrix comprises large-particle lithium cobalt oxide and small-particle lithium cobalt oxide.
4. The lithium cobalt oxide positive electrode material according to claim 3, characterized in that: The particle size of the large-particle lithium cobalt oxide is 15-25 μm.
5. The lithium cobalt oxide positive electrode material according to claim 4, characterized in that: The particle size of the large-particle lithium cobalt oxide is 18-23 μm.
6. The lithium cobalt oxide positive electrode material according to claim 3, characterized in that: The particle size of the small-particle lithium cobalt oxide is 1-5 μm.
7. The lithium cobalt oxide positive electrode material according to claim 6, characterized in that: The particle size of the small-particle lithium cobalt oxide is 3-5 μm.
8. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that: Taking the mass of the doped lithium cobalt oxide matrix as 100%, the content of the ferroelectric is 0.05-0.5%.
9. The lithium cobalt oxide positive electrode material according to claim 8, characterized in that: Taking the mass of the doped lithium cobalt oxide matrix as 100%, the content of the ferroelectric is 0.2-0.5%.
10. The lithium cobalt oxide positive electrode material according to claim 3, characterized in that: The mass ratio of the large-particle lithium cobalt oxide to the small-particle lithium cobalt oxide is z:(1-z), wherein 0.6≤z≤0.
9.
11. A method for preparing a lithium cobalt oxide positive electrode material according to any one of claims 1 to 10, characterized in that: The preparation method comprises the following steps: (1) preparing a doped lithium cobalt oxide polycrystalline material, wherein the doping elements in the doped lithium cobalt oxide polycrystalline material are A and B; (2) The doped lithium cobalt oxide polycrystalline material described in step (1) is mixed with a ferroelectric and then sintered to obtain the lithium cobalt oxide positive electrode material.
12. The preparation method according to claim 11, characterized in that: The doped lithium cobalt oxide polycrystalline material in step (1) includes polycrystalline large lithium cobalt oxide and polycrystalline small lithium cobalt oxide.
13. The preparation method according to claim 12, characterized in that: The preparation method of the polycrystalline lithium cobalt oxide comprises the following steps: a) mixing a large particle size cobalt source, a soluble A salt, a soluble B salt and a lithium source to obtain a first mixture; b) sintering the first mixture to obtain polycrystalline lithium cobalt oxide.
14. The preparation method according to claim 12, characterized in that: The preparation method of polycrystalline lithium cobalt oxide comprises the following steps: a') mixing a small particle size cobalt source, a soluble A salt, a soluble B salt and a lithium source to obtain a second mixture; b') sintering the second mixture to obtain polycrystalline lithium cobalt oxide.
15. The preparation method according to claim 13, characterized in that: The particle size of the large-particle cobalt source in step a) is 15-25 μm.
16. The preparation method according to claim 14, characterized in that: The particle size of the small-particle cobalt source in step a') is 1-5 μm.
17. The preparation method according to claim 13 or 14, characterized in that: The cobalt source in step a) and step a') is cobalt tetraoxide.
18. The preparation method according to claim 17, characterized in that: The cobalt oxide is spherical in shape and has pores inside.
19. The preparation method according to claim 13 or 14, characterized in that: The soluble A salt in step a) and step a') is independently aluminum acetate and / or aluminum nitrate.
20. The preparation method according to claim 13 or 14, characterized in that: The soluble B salt in step a) and step a') is independently any one of the acetates or nitrates of La, Ce, Pr, Nd, Er, Zr, Nb, Sr, V, Ba, Ca, Na and K, or a combination of at least two thereof.
21. The preparation method according to claim 13 or 14, characterized in that: The lithium source in step a) and step a') is independently any one of lithium carbonate, lithium hydroxide, lithium oxide, lithium oxalate or lithium peroxide, or a combination of at least two thereof.
22. The preparation method according to claim 21, characterized in that: The lithium source is a combination of two of lithium carbonate, lithium hydroxide and lithium oxide, and the mass ratio of the two substances is σ:(1-σ), 0.5≤σ<1.
23. The preparation method according to claim 21, characterized in that: The lithium source is a combination of three of lithium carbonate, lithium hydroxide and lithium peroxide, and the mass ratio of the three substances is m:n:(1-mn), 0.5≤m<1, 0 <n<0.5。 24. The preparation method according to claim 13, characterized in that: The mixing described in step a) is carried out in the following manner: the raw materials except the lithium source are mixed in liquid phase, and then mixed with the lithium source after flash evaporation.
25. The preparation method according to claim 14, characterized in that: The mixing described in step a') is carried out in the following manner: the raw materials except the lithium source are mixed in liquid phase, and then mixed with the lithium source after flash evaporation.
26. The preparation method according to claim 13 or 14, characterized in that: The solid content of the slurry obtained by the liquid phase mixing step of the raw materials except the lithium source in step a) and step a') is independently 60-90%.
27. The preparation method according to claim 13 or 14, characterized in that: The sintering in step b) and step b') is carried out in an air atmosphere, and the air flow rate of the sintering is independently 0.8-2.0 L / (min▪m 3 ).
28. The preparation method according to claim 13 or 14, characterized in that: The heating rates of the sintering in step b) and step b') are independently 5-10° C. / min.
29. The preparation method according to claim 13 or 14, characterized in that: The sintering temperatures in step b) and step b') are independently 400-800° C., and the sintering time is independently 1-5 hours.
30. The preparation method according to claim 11, characterized in that: The sintering in step (2) is carried out in an air atmosphere.
31. The preparation method according to claim 30, characterized in that: The air flow rate of the sintering in step (2) is 0.2-1.0L / (min▪m 3 ).
32. The preparation method according to claim 11, characterized in that: The heating rate of the sintering in step (2) is 1-6°C / min.
33. The preparation method according to claim 11, characterized in that: The sintering temperature in step (2) is 800-1100°C.
34. The preparation method according to claim 33, characterized in that: The sintering temperature in step (2) is 950-1100°C.
35. The preparation method according to claim 11, characterized in that: The sintering time in step (2) is 5-20 hours.
36. The preparation method according to claim 35, characterized in that: The sintering time in step (2) is 12-16 hours.
37. The preparation method according to claim 11, characterized in that: The preparation method comprises the following steps: (1) A cobalt source with a particle size of 15-25 μm, a soluble A salt and a soluble B salt are mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 60-90%, the slurry is flash-dried and then mixed with a lithium source, and then the mixture is sintered in an air atmosphere at 400-800°C for 1-5h, the sintering heating rate is 5-10°C / min, and the air flow rate is 0.8-2.0L / (min▪m 3 ), after sintering, the temperature is naturally lowered to 25-100°C to obtain polycrystalline lithium cobalt oxide; A cobalt source with a particle size of 1-5 μm, a soluble A salt and a soluble B salt are mixed and stirred in an aqueous solution to obtain a slurry with a solid content of 60-90%, the slurry is flash-dried and then mixed with a lithium source, and then the mixture is sintered in an air atmosphere at 400-800° C. for 1-5 hours, the sintering heating rate is 5-10° C. / min, and the air flow rate is 0.8-2.0 L / (min▪m 3 ), after sintering, the temperature is naturally lowered to 25-100°C to obtain polycrystalline lithium cobalt oxide; Wherein, the soluble A salt is aluminum acetate and / or aluminum nitrate, and the soluble B salt is any one or a combination of at least two of the acetates or nitrates of La, Ce, Pr, Nd, Er, Zr, Nb, Sr, V, Ba, Ca, Na and K; (2) The polycrystalline large lithium cobalt oxide and the polycrystalline small lithium cobalt oxide described in step (1) are graded, and then the ferroelectric is added and mixed, and the mixture is sintered in an air atmosphere at 800-1100° C. for 5-20 h, the sintering heating rate is 1-6° C. / min, and the air flow rate is 0.2-1.0 L / (min▪m 3 ), and naturally cool to room temperature after sintering to obtain the lithium cobalt oxide positive electrode material.
38. A lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode comprises the lithium cobalt oxide positive electrode material as described in any one of claims 1 to 10.
Citation Information
Patent Citations
Method for testing maximum compaction density of pole piece of material
CN102564894A
Preparation method for modified lithium cobalt oxide capable of being recycled at high cut-off voltage
CN103490063A
A method for preparing lithium cobalt oxide cathode material
CN103746114B
High-voltage lithium cobalt oxide cathode material for lithium-ion battery and preparation method of high-voltage lithium cobalt oxide cathode material
CN105406036A
Preparation method of lithium manganate cathode material with ferri-containing compound coating
CN105826550A